Locked And Tied: Locking Chain And Change Of Problems - Khoirunisa, Alfiah; Kartini; Raihan (Pandawan Sejahtera Indonesia, 2021)
Blockchains are typically named as democratisation technologies, however ever, their relationship with the law and general democratic establishments remains uncertain. First, it compares blockchain technology with the broader theory of transparency. Second, it examines the link between transparency and democracy, and asks how blockchain technology mediates these relationships. Finally, it studies blockchain however technology affects specific manifestations of transparency and freedom of information. The conclusion of this text is that the relationship between transparency and democratic ideals is complex, controversial, and extremely contextual; the “democratized” technical transparency embedded within the blockchain will simply be evidenced in its application. It's undemocratic. while not considering the political gatekeepers and also the legal, social, and cultural desires that support these goals, blockchain technology cannot bring home the bacon the broader goals of transparency.